2014
DOI: 10.1021/jz500328w
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Oscillations in Chlorosome Elucidated by Two-Dimensional Electronic Spectroscopy

Abstract: Chlorosomes are the most efficient photosynthetic light-harvesting complexes found in nature and consist of many bacteriochlorophyll (BChl) molecules self-assembled into supramolecular aggregates. Here we elucidate the presence and the origin of coherent oscillations in chlorosome at cryogenic temperature using 2D electronic spectroscopy. We observe coherent oscillations of multiple frequencies superimposed on the ultrafast amplitude decay of 2D spectra. Comparison of oscillatory features in the rephasing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 63 publications
5
38
0
Order By: Relevance
“…20,182 Indeed, increased attention to the dynamical characteristics of the exciton-phonon coupling has arisen from 2D electronic spectroscopy experiments performed in recent years on several photosynthetic pigmentprotein complexes and in conjugated polymers. [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200] These experiments have in fact unveiled unexpected long-lived quantum coherence effects in the energy migration process, an indication that EET occurs in an intermediate coupling regime. While the actual consequences of quantum coherence in the light-harvesting efficiency of these systems is still subject of a heated debate, understanding the molecular basis sustaining coherence effects have far reaching consequences, e.g.…”
Section: Spectral Densities Disorder and Correlationsmentioning
confidence: 92%
See 1 more Smart Citation
“…20,182 Indeed, increased attention to the dynamical characteristics of the exciton-phonon coupling has arisen from 2D electronic spectroscopy experiments performed in recent years on several photosynthetic pigmentprotein complexes and in conjugated polymers. [183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199][200] These experiments have in fact unveiled unexpected long-lived quantum coherence effects in the energy migration process, an indication that EET occurs in an intermediate coupling regime. While the actual consequences of quantum coherence in the light-harvesting efficiency of these systems is still subject of a heated debate, understanding the molecular basis sustaining coherence effects have far reaching consequences, e.g.…”
Section: Spectral Densities Disorder and Correlationsmentioning
confidence: 92%
“…Often, like in the LHCII complex of plants, the large number of pigments involved make those fittings ambiguous, so other studies, especially in the last years, attempt also the prediction of site energies using the quantum-chemical methods described in Section 2. Due to the recent discovery of long-lasting quantum coherence effects in several photosynthetic complexes, 183,184,[188][189][190][191][192][193][194][195][196][197][198][199][200] which have underscored the importance of the vibrations in the energy transfer process, in the last decade some groups have also pursued the prediction of the spectral density of pigment-protein coupling from simulation (see section 4).…”
Section: Biological Light Harvesting Systemsmentioning
confidence: 99%
“…S1 in the Electronic Supplementary Information (ESI). 23,[40][41] Briefly, the 800 nm pulses of 50 fs duration generated from a 1-kHz regenerative amplified Ti:sapphire laser (Coherent Legend Elite seeded by Vitesse) were converted to visible wavelengths by a home-built noncollinear optical parametric amplifier (NOPA). The broadband NOPA output pulses of 720 nm centre wavelength and 80 nm bandwidth were compressed by a prism compressor.…”
Section: Two-dimensional Electronic Spectroscopymentioning
confidence: 99%
“…The time scale of the anisotropy decay observed in this work is also in good agreement with ultrafast line shape dynamics (20-30 fs) revealed in the 2D spectra of chlorosomes using two-dimensional electronic spectroscopy. 10,13 In those studies, the fast line shape dynamics were attributed to downhill energy transfer through a ladder of exciton states of various energies. Specifically, it was suggested that such ultrafast energy redistribution of initial excitation can occur only within and/or among coherent domains in the close proximity in the same BChl layer, mainly from smaller domains (of high energies) to larger ones (of low energies).…”
Section: 5mentioning
confidence: 99%